The Quest for Stability: The View of Financial Institutions - Hans J. Blommestein; Lex H. Hoogduin; Jolanda J.W. Peeters; Wim W. Boonstra; Verónica Vallés; Christian Weistroffer; Stephan Schulmeister (SUERF - The European Money and Finance Forum, 2010)
On September 3-4, 2009 SUERF and Utrecht University School of Economicsorganized the Colloquium "The Quest for Stability" in Utrecht, the Netherlands. The papers included in this SUERF Study are based on contributions to the Colloquium.
Keywords: E4; E41; E42; E44; E52; F31; F37; G12; G14; G15; G31; G32; H25; 330; Financial crisis; financial innovation; risk management by financial institutions; credit policy; bank business models; risk monitoring; early-warning systems; exchange rate volatility; general transaction tax; Finanzkrise; Finanzmarktregulierung; Regulierung; Welt